Suicide Among Rural Primary School Learners in Zimbabwe: An Epidemic in Need of Mitigation - Chidarikire, Munyaradzi; Chikwati, Takunda; Chidarikire, Jane (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
Suicide among rural primary school learners Zimbabwe has reached epidemic proportions, yet there is dearth. However, the causes and potential mitigation strategies are still limited. This article aims to address that gap by exploring Zimbabwe rural primary learners' perspectives. Using a socio-cultural theoretical framework, this qualitative study will conduct focus group with 12 learners from Mahoto rural area, Masvingo North Constituency to elicit learners' lived experiences and suicide motivations. The data will undergo thematic analysis to identify key patterns and themes. Initial findings suggest that academic struggles without access to counselling drive many rural primary school learners to end their lives prematurely. This highlights the need for Zimbabwe's Government, through the Ministry of Primary and Secondary Education to urgently deploy professional counsellors. By giving voice to the disadvantaged rural learner suicide epidemic firsthand, this study seeks actionable strategies to stem the tragedy of learners’ suicide and promote the well-being of Zimbabwean rural learners.